2017
DOI: 10.1002/solr.201700142
|View full text |Cite
|
Sign up to set email alerts
|

Intermixing Effect on Electronic Structures of TQ1:PC71BM Bulk Heterojunction in Organic Photovoltaics

Abstract: The interface energetics and intermixing effects of the donor/acceptor bulk heterojunction (BHJ) blends of poly[2,3‐bis‐(3‐octyloxyphenyl) quinoxaline‐5, 8‐dilyl‐alt‐thiophene‐2, 5‐diyl]: [6,6]‐phenyl C71butyric acid methyl ester (TQ1:PC71BM) have been investigated using ultraviolet photoemission spectroscopy (UPS) in combination with the integer charge transfer model. The TQ1:PC71BM represents the useful model system for BHJ organic photovoltaics featuring effective charge generation and transport. It finds o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…[20] Our previous work has demonstrated that the charge recombination loss in operating OSCs can be effectively suppressed via heterojunction ICT states, leading to the enhancement of V oc . [20,21] Blend morphologies that possess fine phase separation and molecular packing can create highly effective charge transfer networks in the ternary system, resulting in improved charge transport and thus high device FF. [11,[22][23][24] Ternary architecture is one of the most effective strategies to boost the power conversion efficiency (PCE) of organic solar cells (OSCs).…”
Section: Doi: 101002/adma202002344mentioning
confidence: 99%
See 2 more Smart Citations
“…[20] Our previous work has demonstrated that the charge recombination loss in operating OSCs can be effectively suppressed via heterojunction ICT states, leading to the enhancement of V oc . [20,21] Blend morphologies that possess fine phase separation and molecular packing can create highly effective charge transfer networks in the ternary system, resulting in improved charge transport and thus high device FF. [11,[22][23][24] Ternary architecture is one of the most effective strategies to boost the power conversion efficiency (PCE) of organic solar cells (OSCs).…”
Section: Doi: 101002/adma202002344mentioning
confidence: 99%
“…It is known that the electronic structure at the donor-acceptor interface affects charge generation and transport, and thus device performance. [21] Hence, ultraviolet photoelectron spectroscopy (UPS) is performed to estimate the energy levels of the donors and acceptor ( Figure S3, Supporting Information). The ionization potential (IP) is directly derived from the secondary electron cut-off and the frontier edge of the occupied density of the states.…”
Section: Doi: 101002/adma202002344mentioning
confidence: 99%
See 1 more Smart Citation
“…By UPS depth profiling not only the compositional profile of donor and acceptor could be optained, but also the depth dependent HOMO-HOMO offsets between them were recorded 27 . 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…The energy level alignment at the D:A BHJ interface can be precisely described by the ICT model based on the results from PES (Figure 7) [69] ICT state is related to the smallest energy required to take away one electron (the largest energy gained from adding one electron) from (to) the organic semiconductor molecule at the heterojunction interface producing the fully relaxed state. The values of E ICT+/− are determined by separately conducting UPS measurement on donor and acceptor films deposited on the different substrates with a large range of WFs.…”
Section: Interfacial Electronic Structures In Oscsmentioning
confidence: 99%